Mozambique Social Accounting Matrix, 2007 - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The Mozambique Social Accounting Matrix (SAM), 2007 is built using the supply-use tables from national accounts, government budgets, and balance of payments, and so provides a detailed representation of the Mozambican economy. It separates 33 activities and commodities; labor is disaggregated by education level; and households by rural and urban per capita expenditure quintiles. Information on labor is drawn from the 2008/09 Household Survey. Finally, the SAM identifies government, investment and foreign accounts. It is therefore an ideal database for conducting economywide impact assessments, including SAM-based multiplier analysis and computable general equilibrium (CGE) modeling.